2019
DOI: 10.3390/app9102106
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the Symptoms and Brain Aging in Women with Fibromyalgia: A Cross-Sectional Study

Abstract: Fibromyalgia is a chronic syndrome that is characterized by widespread pain and an altered brain dynamic. The aim of this study was to analyze the effect of the duration of the symptoms on the cortical activity of women with fibromyalgia using electroencephalogram power spectrum analyses in an eye-closed resting state. Twenty-nine women participated in this cross-sectional study (N: 29; age: 55.59 [9.50]). Theta, alpha, beta-1, beta-2, and beta-3 frequency bands were analyzed using EEGLAB. Theta power signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…EEG signals were assessed pre- (one week before starting the intervention) and post-exergame intervention (one week after ending the intervention) with an Enobio device (Neuroelectrics, Cambridge, MA, USA) [36] during a 1-min resting period with eyes closed. This procedure was also followed in previous studies with women with fibromyalgia [10,11]. The wireless Enobio electrode system is reliable even with dry electrodes [37].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EEG signals were assessed pre- (one week before starting the intervention) and post-exergame intervention (one week after ending the intervention) with an Enobio device (Neuroelectrics, Cambridge, MA, USA) [36] during a 1-min resting period with eyes closed. This procedure was also followed in previous studies with women with fibromyalgia [10,11]. The wireless Enobio electrode system is reliable even with dry electrodes [37].…”
Section: Methodsmentioning
confidence: 99%
“…This enabled us to explore whether the duration of fibromyalgia symptoms altered the effectiveness of the exergame-based intervention. This strategy for splitting sub-groups of patients was previously performed in women with fibromyalgia [10,39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, people with FM usually showed depression or cognitive impairment ( Wolfe et al, 2010 ) in several domains such as long-term memory ( Canovas et al, 2009 ), short-term memory ( Park et al, 2001 ), or working memory ( Coppieters et al, 2015 ). These comorbidities could have an impact on EEG, showing a left hemisphere hypoactivation ( Villafaina et al, 2019e ) or a reduced theta power at rest ( Musaeus et al, 2018 ; Villafaina et al, 2019b ). However, taking into account the simultaneous cognitive task, the attention deficit disorder could have a significant impact on the EEG patter during the DT condition.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, FM is accompanied by other symptoms, such as stiffness, mobility problems, sleep disorders, anxiety, depression, or cognitive impairments ( Wolfe et al, 2010 ). The study of cognition and FM is a growing field of research since previous studies have reported cognitive impairments in several domains of people with FM, including long-term memory ( Canovas et al, 2009 ), short-term memory ( Park et al, 2001 ), working memory ( Coppieters et al, 2015 ), processing speed ( Del Paso et al, 2015 ), or even an abnormal EEG signal at rest ( Villafaina et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%